Effectiveness Of Gamified Apps on the Vocabulary Development of Grade 12 Senior High School Students - Santiago, Rina Mae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of gamified applications on the vocabulary development of Grade 12 Senior High School students at Tomas Claudio Colleges during the School Year 2025–2026. Using an experimental research design, the study employed a randomized pretest–posttest control group design involving forty-eight (48) Humanities and Social Sciences (HUMSS) students. The respondents were described according to age, sex, sibling position, number of children in the family, parents’ educational attainment, and monthly family income. A researcher-made vocabulary proficiency test consisting of thirty (30) items was utilized to measure word meaning in context, vocabulary application, and matching type skills. The experimental group was exposed to gamified vocabulary applications, namely Anki and Quizlet, while the control group received traditional vocabulary instruction without gamified elements.Findings revealed that both groups improved in their posttest performance; however, the experimental group obtained significantly higher mean scores compared to the control group. Results of the t-test showed significant differences between the pretest and posttest scores of both groups, confirming the effectiveness of the intervention. Moreover, one-way ANOVA results indicated no significant differences in the posttest performance of the experimental group when grouped according to profile variables, suggesting that gamified learning tools are effective regardless of demographic characteristics.The study concluded that gamified applications significantly enhance students’ vocabulary proficiency, engagement, and motivation. Gamification creates an interactive, learner-centered environment that promotes active participation and long-term retention of vocabulary. It was recommended that teachers integrate gamified applications in vocabulary instruction and that school administrators provide professional development opportunities to support their implementation. Future studies may explore the long-term effects of gamification on other language skills.